Proceso de atención de enfermería en adulto con colesteatoma del oído izquierdo. - Rivera Cali, Jhonny Antonio (2022)
The present clinical case deals with a 44-year-old male patient with cholesteatoma of the left ear who went to the Alfredo Noboa Montenegro Hospital accompanied by his wife for presenting vertigo, hearing loss, tinnitus, ear pain, headache, presenting retroauricular erythema located At the level of the mastoid region, the presence of purulent secretion with a bad smell is observed in the external auditory canal. The patient goes to the hospital because the intensity of the pain together with the vertigo and hearing loss does not allow him to carry out his work and personal activities on a daily basis, the main objective of the clinical case is to execute the nursing care process (PAE) through of the information obtained from the patient for the correct planning and execution of nursing interventions that allow improving functional patterns that are altered. Therefore, physical, blood chemistry, blood count, bacteriology, imaging and audiometry studies were carried out, which helped in the correct treatment of the patient, consisting of: the administration of the drug Paracetamol 1g diluted in 100 ml of sodium chloride at 0.9% every 8 hours and tramadol 100 mg / 2 ml intravenously to relieve pain, removal of serosanguineous fluid and purulent secretions together with asepsis of the external auditory canal, surgical removal by Mastoidectomy or modified radical Mastoidectomy together with postoperative care such as control of vital signs, monitor possible adverse effects of general anesthesia and administration of the prescribed medication.